2022
DOI: 10.20944/preprints202212.0199.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Open Defecation among Rural Women in Ghana: Analysis of 2003, 2008 and 2014 Demographic and Health Surveys

Abstract: The study investigated determinants of open defecation among rural women in Ghana. The study extracted data from the female’s file of the 2003, 2008 and 2014 Ghana Demographic and Health Survey (GDHS). A total of 4,284 pooled sample size of rural women aged 15-49 with complete information about the variables analyzed in the study. The outcome variable was “open defecation” (i.e., defecating in an open space rather than a toilet facility) whilst fourteen (14) key explanatory variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This finding is consistent with a study in Ghana, which found that women with formal education had a decreased likelihood of practicing open defecation compared to those without formal education (AOR = 0.69, 95% CI: 0.56-0.85). 31 In this study, the majority of household heads were farmers residing in rural areas, as indicated in Table 1 , and they exhibited a high prevalence of open defecation practices. This observation aligns with research conducted in Haiti, which similarly noted higher rates of open defecation among farmers and their households.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…This finding is consistent with a study in Ghana, which found that women with formal education had a decreased likelihood of practicing open defecation compared to those without formal education (AOR = 0.69, 95% CI: 0.56-0.85). 31 In this study, the majority of household heads were farmers residing in rural areas, as indicated in Table 1 , and they exhibited a high prevalence of open defecation practices. This observation aligns with research conducted in Haiti, which similarly noted higher rates of open defecation among farmers and their households.…”
Section: Resultsmentioning
confidence: 72%
“…Additional studies corroborate this model assumption, as their findings revealed no indication of poor fit or misspecification. 31 Thus, this analysis was conducted to verify that hypothesized conditions were true.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, investment priorities continue to favour drinking water over sanitation. 8 , 9 In Nigeria, for instance, more than130 million people, constituting two-thirds of the population, lack access to basic sanitation facilities. Similarly, in South Africa, over 18 million people face a similar challenge.…”
Section: Introductionmentioning
confidence: 99%